2013
DOI: 10.1038/npp.2013.65
|View full text |Cite
|
Sign up to set email alerts
|

Hyposensitivity to Gamma-Aminobutyric Acid in the Ventral Tegmental Area During Alcohol Withdrawal: Reversal by Histone Deacetylase Inhibitors

Abstract: Putative dopaminergic (pDAergic) ventral tegmental area (VTA) neurons have an important role in alcohol addiction. Acute ethanol increases the activity of pDAergic neurons, and withdrawal from repeated ethanol administration produces a decreased sensitivity of pDAergic VTA neurons to GABA. Recent studies show that behavioral changes induced by chronic alcohol are reversed by inhibitors of histone deacetylases (HDACs). Whether HDAC-induced histone modifications regulate changes in GABA sensitivity of VTA pDAerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 46 publications
(69 reference statements)
10
62
0
Order By: Relevance
“…One of many examples of this is with Trichostatin A (TSA), a general HDAC inhibitor with antitumor activity (Drummond et al, 2005), that has been shown to decrease the motivation for and intake of addictive drugs (Romieu et al, 2008). Such a finding has been observed with other HDAC inhibitors and variations to the time and route of drug administration (Arora et al, 2013; Kim et al, 2014; Raybuck et al, 2013). …”
Section: Histone-mediated Actions In Drug Addictionsupporting
confidence: 65%
“…One of many examples of this is with Trichostatin A (TSA), a general HDAC inhibitor with antitumor activity (Drummond et al, 2005), that has been shown to decrease the motivation for and intake of addictive drugs (Romieu et al, 2008). Such a finding has been observed with other HDAC inhibitors and variations to the time and route of drug administration (Arora et al, 2013; Kim et al, 2014; Raybuck et al, 2013). …”
Section: Histone-mediated Actions In Drug Addictionsupporting
confidence: 65%
“…Recently, the acetylation state of histones has emerged as a potential epigenetic mechanism in coordinating the effects of alcohol in the brain as well as related behaviors (Wang et al, 2007; Pandey et al, 2008; Pascual et al, 2012; Sakharkar et al, 2012; Arora et al, 2013; Moonat et al, 2013; Warnault et al, 2013). We recently reported that innately higher levels of HDAC2 in the CeA and MeA of P rats was reciprocally correlated with deficits in histone H3 acetylation levels of synaptic plasticity-related genes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin modifications by enzymes such as histone deacetylases (HDACs) also alter gene expression in neurons and neuroplasticity underlying memory formation (Abel and Zukin, 2008;Haggarty and Tsai, 2011). GABA A receptors (GABA A R) are epigenetically regulated in response to early-life stress and addictive drugs (Arora et al, 2013;Kennedy et al, 2013). GABA A R signaling in DA neurons plays a key role in reward-motivated learning (Laviolette and van der Kooy, 2001;Parker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%